2018
DOI: 10.1188/18.onf.96-105
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Outcomes of Genetic Counseling Options in Breast and Ovarian Cancer: An Integrative Review

Abstract: The demand for genetic counseling will grow as advances in cancer genomics reveal genes that may contribute to cancer predisposition. Innovative delivery models are necessary to ensure that all people have access to care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 25 publications
(69 reference statements)
2
33
0
Order By: Relevance
“…When examining the literature specific to genetics consultation via live videoconferencing, the term “telegenetics,” is most often used, but the terms “virtual health” (Weissman, Zellmer, Gill, & Wham, 2018), “televideo” (Voils et al, ), and web‐based/video (National Society of Genetic Counselors, ) were also noted. Collectively, these studies have demonstrated improved access to care in underserved areas with high levels of patient satisfaction and outcomes similar to in‐person consultations across many patient populations and medical indications (Abrams & Geier, ; Bradbury et al, ; Buchanan et al, ; Coelho, Arnold, Nayler, Tischkowitz, & MacKay, ; D'Agincourt‐Canning et al, ; Fournier, Bazzell, & Dains, ; Gattas, MacMillan, Meinecke, Loane, & Wootton, ; Gray et al, ; Hardy & Grinzaid, ; Hawkins, Creighton, Ho, McManus, & Hayden, ; Hilgart et al, ; Hopper, Buckman, & Edwards, ; Kubendran, Sivamurthy, & Schaefer, ; Lea et al, ; Mette et al, ; Otten, Birnie, Lucassen, Ranchor, & van Langen, ; Schwartz et al, ; Solomons, Lamb, Lucas, McDonald, & Miesfeldt, ; Stalker et al, ; Sutphen et al, ; Weissman et al, ; Wenger et al, ; Zilliacus et al, ; Zilliacus, Meiser, Lobb, Kirk, et al, ). Some studies have shown reductions in cost and time per patient for the clinic and/or the patient (Buchanan et al, ; D'Agincourt‐Canning et al, ; Otten, Birnie, Ranchor, & van Langen, ; Schwartz et al, ; Weissman et al, ), shorter wait times (Cohen et al, ; Kubendran et al, ; Stalker et al, ; Weissman et al, ), and a larger geographic reach (Cohen et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When examining the literature specific to genetics consultation via live videoconferencing, the term “telegenetics,” is most often used, but the terms “virtual health” (Weissman, Zellmer, Gill, & Wham, 2018), “televideo” (Voils et al, ), and web‐based/video (National Society of Genetic Counselors, ) were also noted. Collectively, these studies have demonstrated improved access to care in underserved areas with high levels of patient satisfaction and outcomes similar to in‐person consultations across many patient populations and medical indications (Abrams & Geier, ; Bradbury et al, ; Buchanan et al, ; Coelho, Arnold, Nayler, Tischkowitz, & MacKay, ; D'Agincourt‐Canning et al, ; Fournier, Bazzell, & Dains, ; Gattas, MacMillan, Meinecke, Loane, & Wootton, ; Gray et al, ; Hardy & Grinzaid, ; Hawkins, Creighton, Ho, McManus, & Hayden, ; Hilgart et al, ; Hopper, Buckman, & Edwards, ; Kubendran, Sivamurthy, & Schaefer, ; Lea et al, ; Mette et al, ; Otten, Birnie, Lucassen, Ranchor, & van Langen, ; Schwartz et al, ; Solomons, Lamb, Lucas, McDonald, & Miesfeldt, ; Stalker et al, ; Sutphen et al, ; Weissman et al, ; Wenger et al, ; Zilliacus et al, ; Zilliacus, Meiser, Lobb, Kirk, et al, ). Some studies have shown reductions in cost and time per patient for the clinic and/or the patient (Buchanan et al, ; D'Agincourt‐Canning et al, ; Otten, Birnie, Ranchor, & van Langen, ; Schwartz et al, ; Weissman et al, ), shorter wait times (Cohen et al, ; Kubendran et al, ; Stalker et al, ; Weissman et al, ), and a larger geographic reach (Cohen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…access, genetic counseling, genetic services, rural, service delivery, telegenetics, telehealth, telemedicine, telephone counseling, underserved Fournier, Bazzell, & Dains, 2018;Gattas, MacMillan, Meinecke, Loane, & Wootton, 2001;Gray et al, 2000;Hardy & Grinzaid, 2017;Hawkins, Creighton, Ho, McManus, & Hayden, 2013;Hilgart et al, 2012;Hopper, Buckman, & Edwards, 2011;Kubendran, Sivamurthy, & Schaefer, 2017;Lea et al, 2005;Mette et al, 2016;Otten, Birnie, Lucassen, Ranchor, & van Langen, 2016;Schwartz et al, 2014;Solomons, Lamb, Lucas, McDonald, & Miesfeldt, 2018;Stalker et al, 2006;Sutphen et al, 2010;Weissman et al, 2018;Wenger et al, 2014;Zilliacus et al, 2011;Zilliacus, Meiser, Lobb, Kirk, et al, 2010). Some studies have shown reductions in cost and time per patient for the clinic and/or the patient (Buchanan et al, 2015;D'Agincourt-Canning et al, 2008;Otten, Birnie, Ranchor, & van Langen, 2016;Schwartz et al, 2014;Weissman et al, 2018), shorter wait times (Cohen et al, 2013;Kubendran et al, 2017;Stalker et al, 2006;Weissman et al, 2018), and a larger geographic reach (Cohen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, for FDRs in underserviced areas, a telephone-based approach may represent a lowintensity option to provide personalized risk and screening information with health behavioral strategies. [21][22][23] Since the onset of our study, Kinney et al found that, compared with a mailed educational brochure, a telephonebased intervention was effective in improving colonoscopy screening rates in "at-risk relatives" of patients with CRC. 24 They found that greater than one-third of patients in the telephone group who received a personalized CRC risk assessment and counseling session underwent a colonoscopy within 9 months, compared with 16% of controls.…”
Section: Introductionmentioning
confidence: 73%
“…In addition, although brochures have demonstrated some success, they may be less effective than approaches in which a counselor is available to respond to questions and address misinformation or psychosocial issues. Furthermore, for FDRs in underserviced areas, a telephone‐based approach may represent a low‐intensity option to provide personalized risk and screening information with health behavioral strategies …”
Section: Introductionmentioning
confidence: 99%
“…This may affect either the primary or permanent dentition and can range from 5 or fewer missing teeth (hypodontia), 6 or more (oligodontia), to complete absence of teeth (anodontia). Dental agenesis may occur in isolation or as part of a syndrome [7].…”
mentioning
confidence: 99%